Crystal growth, structures and magnetic properties of copper hydroxide compounds with distorted diamond chain magnetic networks. Issue 44 (24th October 2016) - Fujita, Wataru; Tokumitu, Akio; Fujii, Yutaka; Kikuchi, Hikomitsu
Abstract : Single crystals of some copper hydroxides containing diamond chain magnetic networks were obtained by hydrolysis of acetate. Their crystal structure determination and magnetic measurements were carried out. Abstract : Single crystals of copper hydroxide compounds (1–7 ) containing organic sulfonate ions (ethane-1, 2-disulfonate, 1-octanesulfonate, p -toluenesulfonate, p -ethylbenzenesulfonate, 2-naphthalenesulfonate, 1, 5-naphthalenedisulfonate, and 2, 6-naphthalenedisulfonate, respectively) were easily prepared by the hydrolysis of copper acetate aqueous solution containing the respective organic sulfonates. All seven compounds had distorted diamond chain magnetic networks similar to that found in azurite (Cu3 (CO3 )2 (OH)2 ). The diamond chain units were composed of copper, hydroxide, and acetate ions and water molecules (with additional sulfonate ions in the case of7 ). The anions or molecules bridged the neighbouring copper ions, and might mediate superexchange interactions between copper atoms. The chain units did not have the same structure, and were slightly different in their Cu–O bond lengths, Cu–O–Cu bridging angles and so on. Magnetic measurements revealed primarily antiferromagnetic interactions between the neighbouring copper ions and no antiferromagnetic ordering. The χ p vs. T plots showed broad maxima at around 60–80 K that are characteristic of low-dimensional magnetic networks. Compounds1–6 were paramagnetic down to 2 K, while7 had a diamagnetic ground state. The different magnetic properties are due to the small structural differences in the diamond chain units, because the sign and intensity of magnetic coupling between the neighbouring copper ions are sensitive to the bridging structures. Copper hydroxide compounds with different organic ions and diverse structures prepared by this hydrolysis method will facilitate the systematic study of the underlying diamond chain magnetic networks.